Simulasi Penggunaan Ipv6 Pada PD. Pumas Jaya Menggunakan Metode Manual Tunneling - Elidjen, Elidjen; Tanun, Shellyana; Santoso, Budi; Citronegoro, Cipto (ComTech: Computer, Mathematics and Engineering Applications, 2010)
Internet usage trends with IPv4 addresses that only have 32-bit addresses could no longer cope with the large allocation of the required addresses. Internet Engineering Task Force (IETF) has issued a new standard of Internet protocol called IPv6 to anticipate this problem. PD. Pumas Jaya, which started in 1996 in the field of marine products in particular marinated seafood, such as salted fish, rebon shrimp, cuttlefish, anchovies and other marine products to anticipate the need for this in its network. However, IPv6 can not simply be used to replace IPv4 as the existing network infrastructure with IPv4. This research discussed IPv6 simulation tunneling with manual methods so that an IPv6 site can communicate with other IPv6 site even if separated by an infrastructure that supports only IPv4.